2023
DOI: 10.1109/jtehm.2023.3250700
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Point-of-Care Diagnostics for COVID-19 Based on Acoustics and Symptoms

Abstract: Background: The COVID-19 pandemic has highlighted the need to invent alternative respiratory health diagnosis methodologies which provide improvement with respect to time, cost, physical distancing and detection performance. In this context, identifying acoustic bio-markers of respiratory diseases has received renewed interest. Objective: In this paper, we aim to design COVID-19 diagnostics based on analyzing the acoustics and symptoms data. Towards this, the data is composed of cough, breathing, and speech si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Among these algorithms, Random Tree and Naïve Bayes demonstrated the most successful performance in predicting CVD. Chetupalli, S. R. et al [15], introduced a prediction model for COVID-19 based on acoustic signals and patient symptoms, employing different algorithms. The model utilizes breathing audio, speech audio, and cough audio as inputs for logistic regression and support vector machine (SVM) algorithms to generate results.…”
Section: Literature Surveymentioning
confidence: 99%
“…Among these algorithms, Random Tree and Naïve Bayes demonstrated the most successful performance in predicting CVD. Chetupalli, S. R. et al [15], introduced a prediction model for COVID-19 based on acoustic signals and patient symptoms, employing different algorithms. The model utilizes breathing audio, speech audio, and cough audio as inputs for logistic regression and support vector machine (SVM) algorithms to generate results.…”
Section: Literature Surveymentioning
confidence: 99%
“…In contrast to most chronic conditions diagnosed through lab tests, mental disorders rely on self-disclosure through specialized methods, highlighting the intricate nature of mental health data. In the past decades, machine learning (ML) and deep learning (DL) have provided a new paradigm for gaining knowledge from complex data [10] , [11] and numerous ML and DL-based techniques have been developed for healthcare applications including mental healthcare and achieved considerable success [12] , [13] , [14] , [15] , [16] . Specifically, studies are using adjunctive data for the detection of ADHD, including magnetic resonance imaging (MRI) [17] , electroencephalography (EEG) [18] and electrocardiograms (ECG) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…A classification was made between a dry cough and wet cough by applying some modern and traditional machine learning methods to the COUGHVID database, where it has been shown that the decision tree models are superior to the rest of the models in terms of overall performance [15]. Based on logistic regression and support vector machines for acoustic data, and decision tree models for symptoms data, the researchers [16] proposed a multi-modal diagnostic for COVID-19. Using Coswara dataset, an AUC of 0.92 has been reached.…”
Section: Introductionmentioning
confidence: 99%